Activation of AZIN1 RNA editing is a novel mechanism that promotes invasive potential of cancer-associated fibroblasts in colorectal cancer. (1st March 2019) - Takeda, Sho; Shigeyasu, Kunitoshi; Okugawa, Yoshinaga; Yoshida, Kazuhiro; Mori, Yoshiko; Yano, Shuya; Noma, Kazuhiro; Umeda, Yuzo; Kondo, Yoshitaka; Kishimoto, Hiroyuki; Teraishi, Fuminori; Nagasaka, Takeshi; et al.
Abstract: Adenosine-to-inosine (A-to-I) RNA editing is a recently described epigenetic modification, which is believed to constitute a key oncogenic mechanism in human cancers. However, its functional role in cancer-associated fibroblasts (CAFs) within the tumor microenvironment (TME) and its clinical significance remains unclear. Herein, we systematically analyzed a large cohort of 627 colorectal cancer (CRC) specimens, and investigated the expression pattern of ADAR1 and its biological significance on the antizyme inhibitor 1 ( AZIN1 ) RNA editing levels. Both ADAR1 expression and AZIN1 RNA editing levels were significantly elevated in CRC tissues vs. normal mucosa, and these findings correlated with the increased expression of mesenchymal markers, Vimentin (ρ = 0.44) and Fibroblast activation protein (ρ = 0.38). Intriguingly, ADAR1 expression was specifically upregulated in both cancer cells and fibroblasts from cancerous lesions. Conditioned medium from cancer cells led to induction of ADAR1 expression and activation of AZIN1 RNA editing in fibroblasts (p < 0.05). Additionally, edited AZIN1 enhanced the invasive potential of fibroblasts. In conclusion, we provide novel evidence that hyper-editing of AZIN1 enhances the invasive potential of CAFs within the TME in colon and is an important predictor of tumor invasiveness in CRC. Highlights: Hyper-editing of AZIN1 RNA is a frequent event in colorectal cancer-associated fibroblasts (CAFs). Increased AZIN1 RNA editing in CAFs promotes invasion in colorectal cancer tumor microenvironment. AZIN1 RNA editing level in CAFs may be a potential therapeutic target in colorectal cancer.